Empowerment Of Kader Mantap (Independent, Skilled, Adaptive) With Victor Vroom's Theory Approach To Realize Families Aware Of Exclusive Breastfeeding In Sembahe Baru Village - Nainggolan, Anna Waris; Tetti Seriati Situmorang; Parningotan Simanjuntak; Iqra Manisah; Jasica Pratini; Edy Marjuang Purba (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The coverage of exclusive breastfeeding in Sembahe Baru Village has not met the target (<70%). Limitations in manpower and time among health center staff or healthcare workers in Sembahe Baru Village hinder their ability to educate, monitor, and motivate mothers in providing exclusive breastfeeding. Additionally, many cadres remain inactive, and postpartum mothers often lack knowledge about exclusive breastfeeding, making them easily influenced by others. The community engagement activities were conducted in several stages: preparation, socialization of the community engagement activities, and surveys for collecting supporting data; training on using the ASIVroom application; application implementation; and monitoring progress and evaluation. Cadre training was conducted using Victor Vroom's theoretical approach to enhance cadre motivation. This approach emphasizes three key concepts: (1) Expectancy: The belief that a given effort will result in a desired behavior. (2) Valence: The value or significance of the outcomes resulting from specific behaviors, perceived as motivational force by individuals. (3) Instrumentality: The perception that achieving the first-level or best outcome will lead to further results. The ASIVroom application was introduced to breastfeeding mothers, cadres, and healthcare workers, enabling them to utilize the application effectively. Statistical analysis revealed that the education provided significantly improved mothers' knowledge about exclusive breastfeeding (p < 0.05). Evaluation of partner skills indicated that:(1) 62.5% of cadres found the ASIVroom application easy to use. (2) 53.1% rated the accessibility of information within the application as good.